Moral Sensitivity of Indonesian Migrant Workers in Malaysia - Wati, Ratna Kartika; Osman, Zuraini Jamil (Universitas Muhammadiyah Purwokerto, 2025)
As neighbouring countries, Indonesia and Malaysia continue to compete in the economic field, competing to become developed countries. The number of Indonesian citizens who become Indonesian Migrant Workers as domestic assistants in Malaysia, gives a negative stigma to the image of the Indonesian State. This research is a descriptive qualitative research using an interactive analysis model. The conclusion that can be drawn in this study is that, Indonesian Migrant Workers have moral sensitivity formed from several dimensions, namely: moral awareness (awareness of his position, as an Indonesian migrant worker who adheres to the principles of justice, mutual cooperation, responsibility and respect for others), moral decisions (migrant workers always try to commit and keep promises or be trusted by employers / leaders and be respectful and loyal to new colleagues and families in Malaysia), Moral Intention (Indonesian migrant workers try to show their integrity and try to pursue their excellence), moral action (Indonesian migrant workers try to maintain honest behaviour and the good name of individuals and the country of Indonesia. Meanwhile, the main factors affecting the sensitivity of Indonesian migrant workers in Malaysia are that many Indonesian migrant workers are not old enough, Indonesian migrant workers have incomplete population administration, there are illiterate Indonesian migrant workers, Indonesian migrant workers have a history of illness and Indonesian migrant workers are pregnant. In addition, another factor that is thought to affect the moral sensitivity of Indonesian migrant workers in Malaysia is the cost of becoming a migrant worker which is quite expensive, thus encouraging migrant workers to take shortcuts by becoming illegal migrant workers.